1976
DOI: 10.1111/j.1365-2133.1976.tb00862.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma volume, intravascular albumin and its transcapillary escape rate in patients with extensive skin disease

Abstract: Plasma volume and plasma concentration and transcapillary escape rate of albumin (TER alb), i.e. the fraction of intravascular mass of albumin that passes to the extravascular space per unit time, were determined using 125I-labelled human albumin in eight patients with extensive skin disease. Plasma volume and plasma albumin concentration were reduced (P less than 0-05). Thus the intravascular albumin mass was moderately decreased to an average of 0-55 +/- 0-06 (s.d.) g/cm height compared with a normal mean va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
6
0

Year Published

1977
1977
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 12 publications
3
6
0
Order By: Relevance
“…This is consistent with high lymph/plasma protein concentrations in anurans (Conklin 1930a;Bashir 1966;Middler et al 1968;Hillman et al 1987). Vascular exchange of proteins in humans has been estimated at 0.05%-0.1% of V p min Ϫ1 (Pritchard et al 1955;Walker et al 1960;Parving et al 1976). Skov and Steffensen (2003) report turnovers of 0.1% min Ϫ1 from the primary to secondary circulation in cod, while Nichols (1987) estimated plasma exchange of proteins in trout at 0.8% V p min Ϫ1 .…”
Section: Plasma Turnover and Fluid Compartmentssupporting
confidence: 62%
“…This is consistent with high lymph/plasma protein concentrations in anurans (Conklin 1930a;Bashir 1966;Middler et al 1968;Hillman et al 1987). Vascular exchange of proteins in humans has been estimated at 0.05%-0.1% of V p min Ϫ1 (Pritchard et al 1955;Walker et al 1960;Parving et al 1976). Skov and Steffensen (2003) report turnovers of 0.1% min Ϫ1 from the primary to secondary circulation in cod, while Nichols (1987) estimated plasma exchange of proteins in trout at 0.8% V p min Ϫ1 .…”
Section: Plasma Turnover and Fluid Compartmentssupporting
confidence: 62%
“…We found no correlation between the involved skin area and any ofthe above mentioned parameters.The possible mechanisms in the reduction of the plasma volume and the IVM are discussed. It is suggested that reduced IVM may refiect reduced total albumin mass due to lowered rates of albumin synthesis or increased rates of turnover.As a group patients with extensive skin disease have reduced intravascular albumin mass with both low plasma albumin concentration and low plasma volume, although both variables are not reduced in all cases (Parving, Worm & Rossing, 1976). We suggested displacement of albumin into the skin and loss of albumin from the skin to be the dominating mechanisms responsible.…”
mentioning
confidence: 77%
“…As a group patients with extensive skin disease have reduced intravascular albumin mass with both low plasma albumin concentration and low plasma volume, although both variables are not reduced in all cases (Parving, Worm & Rossing, 1976). We suggested displacement of albumin into the skin and loss of albumin from the skin to be the dominating mechanisms responsible.…”
mentioning
confidence: 77%
“…In noncirrhotic patients with chronic disease states (hypertension, heart failure), transcapillary albumin escape is increased, but the extravascular albumin mass is constant due to concomitant increased lymphatic return of albumin to plasma . However, in patients who undergo major surgical procedures or have severe forms of injury or infection, this increase in lymphatic albumin return is often unable to keep up with the transcapillary losses found . Evaluations of the disposition of albumin in surgical patients are further complicated by albumin losses to wound sites.…”
Section: Commentmentioning
confidence: 99%